Improving Inventory Management of Organizational and Individual Equipment at Central Issue Facilities - Carol E. Fan, Elvira N. Loredo (RAND Corporation, 2013)
More than 90 Central Issue Facilities (CIFs) located at major installations around the world issue Organizational Clothing and Individual Equipment (OCIE) to Active Component soldiers and deploying National Guard and Army Reserve soldiers. The value of OCIE inventory held at CIFs in the continental United States (CONUS) increased by 33 percent between January 2007 and August 2010. The Army does not have a standard, data-driven approach for CIF inventory management. Likely as a result, there has been a perception that many CIFs have significantly more inventory than required to meet soldier needs. Army logistics leaders asked RAND to help the Army improve OCIE inventory management while maintaining high levels of soldier support. This report addressed our twofold recommendations for improving the efficiency of inventory management at the CIFs: (1) use a data-driven approach to help CIF managers make replenishment decisions and (2) increase the use of existing inventory through lateral transfers. The report also includes appendixes designed specifically for readers with a detailed knowledge of and experience in CIF inventory management. The appendixes provide an in-depth description of the CIF inventory levels–setting process, including which items to order, when to order, and how much to order. They also describe the CIF retention levels–setting process and address how to identify materiel that is available for lateral transfer. CIF inventory management personnel will find this report useful for gaining more detailed knowledge of the input files and how the RAND-developed algorithms work, allowing those who participate in setting CIF inventory levels and coordinating lateral transfers to understand the underlying methods used to set inventory levels. This project was sponsored by the Deputy Chief of Staff, G-4, U.S. Army Materiel Command. The research was conducted in RAND Arroyo Center’s Military Logistics Program. RAND Arroyo Center, part of the RAND Corporation, is the United States Army’s federally funded research and development center (FFRDC) for policy studies and analyses.